2005
DOI: 10.1159/000082006
|View full text |Cite
|
Sign up to set email alerts
|

Home Hemodialysis and Remote Monitoring: Current Technology, Requirements and Capabilities

Abstract: The changing patterns of utilization of home hemodialysis (HHD) are reviewed with special reference to the factors responsible for its decline and recent revival. Equipment and monitoring systems dedicated to HHD have been recently introduced in response to the demand for more frequent therapies at home. The advantages and disadvantages of novel technology versus time-tested, reliable and versatile platforms are discussed. Despite the significant technological progress achieved, much remains to be done in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This could extend beyond support to intervention if needed. For example, the measures for dealing with hypotension could be triggered remotely by monitoring staff, or monitoring staff could call for an ambulance if they detect that something is wrong and do not get a response from the patient, as discussed by Schlaeper and Diaz-Buxo [ 9 ]. As well as remote monitoring, D1 highlighted the possibility of clinicians sending messages to the patient via the system and two patients proposed that the system should be able to automatically record and upload information required by clinicians for tracking their progress over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could extend beyond support to intervention if needed. For example, the measures for dealing with hypotension could be triggered remotely by monitoring staff, or monitoring staff could call for an ambulance if they detect that something is wrong and do not get a response from the patient, as discussed by Schlaeper and Diaz-Buxo [ 9 ]. As well as remote monitoring, D1 highlighted the possibility of clinicians sending messages to the patient via the system and two patients proposed that the system should be able to automatically record and upload information required by clinicians for tracking their progress over time.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies of professionals’ attitudes [ 4 , 5 ] focus principally on patient outcomes, a US study [ 9 ] found that the main concern that nephrologists have when motivating patients to go on HHD was patient safety. An Australian study of patients and their carers [ 10 ] also found that patients value survival and convenience in choosing treatment, a finding echoed by Cafazzo et al [ 11 ] in their study of nocturnal HHD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, telemedicine can eliminate distance barriers and can improve access to medical services [5]. Equipment and monitoring system dedicated to home hemodialysis have been recently introduced in response to the demand for more frequent therapies at home [6]. In a paper published by Cafazzo et al [7], the availability of RM leads to an increased interest in home hemodialysis and lowered patients’ perceived barriers, such as anxiety and lack of self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Concerns also exist regarding the complexity of home HD 18 and patient safety while performing unsupervised HD at home. 18 20 …”
Section: Introductionmentioning
confidence: 99%